Seasonal food availability calendars for Malaita, Solomon Islands - Alliance of Bioversity International and CIAT; World Vision (2024)
Seasonal foods availability calendars were participatorily developed with members of Siwapo, Oau, Elliote, Maniache and Tauweiseu communities in Malaita, Solomon Islands. The calendars showcase locally available foods, providing information that can be used to empower local communities to improve their access and utilization of diverse foods all year-round using locally available foods. The calendars were developed by the Alliance of Bioversity International and CIAT within the framework of the “Melanesia Rural Market and Innovation Driven (MERMAID) programme, in partnership with world vision. An effort funded by the International Fund for Agricultural Development (IFAD).